(untitled) (Research, Society and Development, 2021)
The healing process is a cascade of cellular events aimed at recovering the physical integrity of a tissue, a natural healing process caused by injuries, burns, accidents, cuts or tears. When discussing the teaching of cell biology, it is difficult to observe proposals that use the healing process as a theme for the study of cytology. This research aims to investigate the previous conceptions of some in the 9th grade of elementary school about the healing process of a wound and the possible relationships between perceptive hair and cell biology. A research was carried out in a public school in the city of Palmeira das Missões, RS, which had the participation of 30 students, distributed in two groups of the 9th grade, aged between 14 and 18 years. The research is qualitative in nature, through a case study and count with a application of a semi-structured questionnaire. The results of this form are analyzed in the content analysis of Bardin (2011) and establish a high relationship that the students create from the healing process of a wound with the past experiences and the daily lives of each one. The results also state that some of them present random and simplified concepts of the wound healing process.